1995
DOI: 10.1046/j.1468-2982.1995.015003211.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cerebrovascular pCO2 Reactivity in Migraine with Aura- a Transcranial Doppler Study During Hyperventilation

Abstract: Cerebrovascular reactivity during hypocapnia was tested in 20 migraineurs (8 with aura, 12 without aura) and 30 sex- and age-matched healthy subjects, and during nitroglycerin-induced headache in 12 healthy subjects. Before and during hyperventilation, mean blood-flow velocity (Vmean) in the middle cerebral artery was measured with transcranial Doppler. In each subject a pCO2 reactivity index (RI) was calculated as (delta Vmean/baseline Vmean)/delta pCO2. Interictally, patients with migraine with aura showed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…101,102 Others suggest a decreased CVR in migraineurs compared with controls, 103 one being restricted to the posterior circulation in MA. 104 When investigating CVR in response to hypocapnia, Thomsen et al and Fiermonte et al reported increased reactivity in MA compared with MO and controls, 105,106 whereas Totaro et al found no difference between migraineurs and controls. 103 The contrasting results may be due to the variations in methods (eg, hypercapnia or hypocapnia, middle or posterior cerebral vasculature) and patient characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…101,102 Others suggest a decreased CVR in migraineurs compared with controls, 103 one being restricted to the posterior circulation in MA. 104 When investigating CVR in response to hypocapnia, Thomsen et al and Fiermonte et al reported increased reactivity in MA compared with MO and controls, 105,106 whereas Totaro et al found no difference between migraineurs and controls. 103 The contrasting results may be due to the variations in methods (eg, hypercapnia or hypocapnia, middle or posterior cerebral vasculature) and patient characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by a population-based twin survey [15]. Other studies have demonstrated differences in regional cerebral blood flow [16], carbon dioxide cerebrovascular reactivity [17], oestrogen profile [18], amino acid metabolism [19], platelet content and serotonin secretion [20].…”
Section: Discussionmentioning
confidence: 80%
“…The finding of increased CVR is unusual given that CVR is usually decreased in the majority of pathologic conditions in which cerebrovascular physiology is altered with the exception of migraine headaches (Thomsen et al 1995). This exception is particularly interesting given that headache is a commonly reported symptom in patients following concussion.…”
Section: Discussionmentioning
confidence: 99%